The angel makers - Harris, Tessa (Constance Piper mysteries, 2018)
"In Victorian England, clairvoyant flower seller Constance Piper goes searching for the truth behind a new rash of murders in London's East End. With the aid of Detective Constable Hawkins, Constance links the mysterious death of a young prostitute to Mother Delaney's vile trade as a baby farmer"--Provided by publisher.